Determinants of intention for subscribing takaful in Kelantan: a study at Kem Batalion 8 Gerakan Am PDRM Malaysia - Muhammad Fadhil Aiman, Munawir (2022)
In Malaysia, the emergence of the Takaful sector offers an alternative-ways as a Shariabcompliant risk management rather than conventional insurance. This study examines the variables that affect Kelantan government servant intentions to subscribe Takaful. Although there are distinctions between conventional insurance and Takaful in terms of the contract, both products aim to safeguard participants and lessen their financial burden in the event of difficulties or accidents. In this regard, how much do Malaysians, particularly Muslims, tolerate takaful items, and how well-informed are consumers about the available options? Despite the fact that Takaful complies with Shariah, the number of participants, particularly among Muslims, is relatively low. Thus, the goal of this study is to determine the variables influencing Kelantan government servants' inclination to subscribe to Takaful. 217 technical staff members who worked at Kem Batalion 8 Gerakan Am PDRM Malaysia in Kelantan participated in the study. Using Pearson Correlation Analysis, One-way ANOVA, and T-test analysis, all hypotheses in this study are examined. The findings demonstrate a significant positive association between product characteristics and several demographic factor and the intention to purchase Takaful. It is believed that this study's findings will aid in the growth of Malaysia's Takaful industry.